Primera detección de Candidatus Rickettsia colombianensi en el departamento del Meta, Colombia (2019)
Introduction: Rickettsia is a genus of Gram-negative obligate intracellular bacteria that cause several epidemics around the world and are transmitted mainly by ticks, fleas, lice and mites. Rickettsiosis is a re-emergent infectious disease without epidemiological surveillance in Colombia. Until few years ago, Rickettsia rickettsi was the only tick-borne Rickettsioses in America; however, new species are being described, and although their pathogenicity has not been confirmed, they should be considered as potential pathogens. Objective: The aim of this study was to determine the presence of rickettsial agents in ticks in the state of Meta, Colombia. Material and Methods: A descriptive cross-sectional study was conducted; ticks were collected and, after their taxonomic identification, gltA, ompA and ompB genes were amplified and sequenced. Results: A total of 169 pools were obtained to which PCR were carried out, of which 2 PCR were amplified for the gltA, ompA and ompB genes. Conclusions: These results demonstrate the presence of Rickettsia spp in ticks in the State of Meta. © 2019 Universidad de Ciencias Medicas de La Hab. All rights reserved.